Induction of both local immune response in mice and protection in a rabbit model by intranasal immunization with modified vaccinia ankara virus expressing a secreted form of bovine herpesvirus 1 glycoprotein D - Del Medico Zajac, Maria Paula; Zanetti, Flavia Adriana; Federico, Carlos Rodolfo; Zabal, Osvaldo Alfredo; Valera, Alejandro Rafael; Calamante, Gabriela (2017)
In this study, we evaluated the immunogenicity and efficacy of mucosal delivery of a recombinant modified vaccinia Ankara virus (MVA) expressing the secreted version of bovine herpesvirus type 1 (BoHV-1) glycoprotein D (MVA-gDs) without addition of adjuvant in two animal models. First, we demonstrated the capability of MVA-gDs of inducing both local and systemic anti-gD humoral immune response after intranasal immunization of mice. Then, we confirmed that two doses of MVA-gDs administered intranasally to rabbits induced systemic anti-gD antibodies and conferred protection against BoHV-1 challenge. Our results show the potential of using MVA as a vector for the rational design of veterinary vaccines capable of inducing specific and protective immune responses both at local and systemic level.